2012
DOI: 10.2967/jnumed.111.101295
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Proteasome Inhibition in Anaplastic Thyroid Carcinoma

Abstract: The ubiquitin-proteasome pathway has been identified as a potential molecular target for cancer therapy. In this study, we investigated the effect of the proteasome inhibitor bortezomib on anaplastic thyroid carcinoma (ATC) characterized by complete refractoriness to multimodal therapeutic approaches. Methods: The ATC cell lines C643 and SW1736 were treated with bortezomib (1 nM to 1 mM) for 12-72 h. Thereafter, growth inhibition was analyzed by thymidine uptake experiments and determination of the viable cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Proteosome inhibitors have also been investigated in the context of ATC as antitumor agents (38,39). Our results demonstrate that both drugs when used in combination significantly decrease tumor growth and induce tumor cell death in vitro and in vivo (Figures 4 -6 and Supplemental Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 50%
“…Proteosome inhibitors have also been investigated in the context of ATC as antitumor agents (38,39). Our results demonstrate that both drugs when used in combination significantly decrease tumor growth and induce tumor cell death in vitro and in vivo (Figures 4 -6 and Supplemental Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 50%
“…Bortezomib, the first inhibitor of the UPP to be used in clinical studies, has been extensively studied for both hematological and solid cancers, including thyroid cancer (Hideshima et al 2001, Papandreou et al 2004, Mitsiades et al 2006, Altmann et al 2012, Wunderlich et al 2012. Results of recent preclinical studies have also indicated that bortezomib inhibits ATC cell proliferation and induces caspase-dependent apoptosis in vitro, with potent antitumor effects in vivo as well (Mitsiades et al 2006, Conticello et al 2007, Altmann et al 2012, Wunderlich et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Results of recent preclinical studies have also indicated that bortezomib inhibits ATC cell proliferation and induces caspase-dependent apoptosis in vitro, with potent antitumor effects in vivo as well (Mitsiades et al 2006, Conticello et al 2007, Altmann et al 2012, Wunderlich et al 2012. The clinical efficacy of bortezomib, however, is challenged by the rapid development of drug resistance, as it is not an irreversible proteasome inhibitor like carfilzomib, and also by the dose-limiting neurotoxicity associated with bortezomib treatment (Ruckrich et al 2009, Jain et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Proteosome inhibitors, such as bortezomib, have been shown to aid apoptosis and decrease tumor proliferation in preclinical studies [34].…”
Section: Tumor Biology and Targeted Therapymentioning
confidence: 99%